People like her : a novel - Lloyd, Ellery (Harper, an imprint of HarperCollinsPublishers, 2021)
A successful media influencer's morally questionable relationship with the truth exposes deep psychological cracks in her marriage at the same time her family is targeted by a violently obsessed fan.